The Influence of Financial Literacy, Lifestyle and Financial Planning on Consumptive Behavior In Millennials and Generation Z - BriLatifa Paramita, Brilianti; Santi Paramita, V. (Publisher Cv. Inara, 2024)
This research aims to examine the influence of financial literacy, lifestyle, and financial planning on consumptive behavior in the millennial and Generation Z. The instruments in this study have passed validity and reliability tests, where these instruments are used as data collection tools. The number of respondents involved in this research is 95 people, dominated by [insert information about the dominant group]. Data collection technique uses random sampling, which falls under probability sampling. The data analysis technique used is descriptive analysis and regression analysis with the assistance of SPSS version 26. Out of the four hypotheses in this research, all are supported by empirical data. The findings of this research explain that financial literacy, and financial planning not influence on consumptive behavior in the millennial and Generation Z. Meanwhile lifestyle have an impact on consumptive behavior in the millennial and Generation Z. What sets this research apart from previous studies is the use of the evaluated objects, which influences the design of specific and unique research instruments. This research conducts descriptive hypothesis testing that was not present in previous studies. Meanwhile, the sample size, sample determination technique, and data analysis technique can be adjusted by future researchers based on the evaluated objects. The results of this research are also beneficial for the managers of the evaluated objects concerning the design of relevant strategies or programs to improve the quality attributes of the evaluated objects.